2012
DOI: 10.1080/15389588.2012.661111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vehicle Impact Velocity, Vehicle Front-End Shapes on Pedestrian Injury Risk

Abstract: The vehicle impact velocity and vehicle front-end shape are 2 dominant factors that influence the pedestrian kinematics and injury severity. A significant reduction of all injuries can be achieved for all vehicle types when the vehicle impact velocity is less than 30 km/h. Vehicle designs consisting of a short front-end and a wide windshield area can protect pedestrians from fatalities. The results also could be valuable in the design of a pedestrian-friendly vehicle front-end shape. [Supplementary materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 24 publications
9
37
1
Order By: Relevance
“…Regarding factor 2, studies of the influence of vehicle type (Ballesteros et al 2004;Roudsari et al 2004) or shape on resulting lesions were likewise based on real-world crash data (Crandall et al 2002;Henary et al 2003;Mallory et al 2012;Martin et al 2011;Otte 1999); there have also been studies using simulations, which have the advantage of being able to take body kinematics after impact into account (Crocetta et al 2015;Gupta and Yang 2013;Han et al 2012;Okamoto et al 2003). Impact against the ground or secondary obstacles has been less studied, mainly due to lack of precise observations and the wide variety of possible obstacles (Badea-Romero and Lenard 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding factor 2, studies of the influence of vehicle type (Ballesteros et al 2004;Roudsari et al 2004) or shape on resulting lesions were likewise based on real-world crash data (Crandall et al 2002;Henary et al 2003;Mallory et al 2012;Martin et al 2011;Otte 1999); there have also been studies using simulations, which have the advantage of being able to take body kinematics after impact into account (Crocetta et al 2015;Gupta and Yang 2013;Han et al 2012;Okamoto et al 2003). Impact against the ground or secondary obstacles has been less studied, mainly due to lack of precise observations and the wide variety of possible obstacles (Badea-Romero and Lenard 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since pedestrian head response depends highly on the accident conditions Watanabe et al 2012;Han et al 2012;Elliote et al 2012;Subit et al 2008), including multiple factors such as vehicle impact speed, vehicle type and geometry, human anthropometry, pedestrian initial position and direction to the vehicle, and their postures, the distribution of these accident conditions in field data and their effects on pedestrian response and injury are summarized here.…”
Section: Pedestrian Accident Conditionsmentioning
confidence: 99%
“…Roudsari et al (2005) found chest and abdomen injuries were more common in pedestrians struck by LTVs. Also, simulation studies (Watanabe et al 2012;Han et al 2012) using FE human models (THUMS) and detailed FE vehicle models showed different pedestrian kinematics and injury risk caused by vehicle types. Han et al (2012) found vehicle designs with a short front-end and a wide windshield area can protect pedestrians from fatalities.…”
Section: Vehicle Designmentioning
confidence: 99%
See 2 more Smart Citations